Gender and sexuality in mental health: perspectives on lesbians, gays, bisexuals, and transgender (LGBT) rights and mental health in the ASEAN region - Alibudbud, Rowalt (Frontiers in Sociology, 2023)
This perspective piece focuses on and analyzes several lesbians, gays, bisexuals, and transgender (LGBT) individuals' rights and their limitations in the Association of Southeast Asian Nations (ASEAN) region, including the limited recognition of self-determined gender identity, limited legal provisions for LGBT marriage, inadequate anti-discrimination policies, and the criminalization of homosexuality. These inadequacies in LGBT rights may stem from colonial, religious, and cultural factors. Moreover, these limited LGBT rights and their societal repercussions may contribute to the minority stress of LGBT individuals, leading to their higher rates of mental health problems. Thus, there may be a need to uphold, recognize, and protect LGBT rights as the region pursue equitable mental health. Toward this pursuit, the region may possibly benefit from culturally adapting gender-affirming practices, increasing their social support, opposing the practice of conversion therapy, and decriminalizing homosexuality. It may also be necessary to explore, analyze, and study the intersection of LGBT identity and mental health, especially longitudinal and interventional studies.